Landschaftsgedächtnis und Geschlechterdiskurse in ausgewählten Werken von Elsa Bernstein und Maria Waser - Monika Mańczyk-Krygiel (Góry, Literatura, Kultura)
This article analyzes the mutual interpenetrations of different types of cultural memory in literary texts, in particular landscape memory, myth memory, and memory of gender stereotypes.